Vocal Signatures For Species Identification Among Eight Microhylid Frogs in Sarawak, Malaysia - Amram, Muhammad Fadzil; Zainudin, Ramlah (Malaysian Applied Biology, 2026)
The advertisement calls of frogs serve as vital communication signals, playing a significant role in species recognition and mate attraction, representing a critical aspect of their behavioural ecology. This study aims to document and analyse the advertisement calls of eight Microhylidae species in various habitats across Sarawak. Using field recordings and acoustic analysis, distinct call characteristics were identified, including frequency, note repetition rate, and pulse structure. Advertisement calls were recorded and analysed using SoundRuler Acoustic Analysis and Praat Acoustic Software. Call characteristics were subsequently compared for species differentiation. The results showed that each species exhibits distinct call characteristics, likely reflecting adaptations to habitat acoustics and conspecific interactions. Among them, Microhyla nepenthicola Das & Haas, 2010 demonstrated the highest rate of note repetition, the greatest number of pulsed notes per call, and the highest dominant frequency, suggesting unique acoustic adaptations within its ecological niche. These findings can contribute to the understanding of species-specific vocalisations and their potential role in mate selection, territorial defence, and environmental adaptation.